High vaulted corridors - Mumbai Archive Project Team (Jio Institute, 2024)
The Aga Khan Maqbara is renowned for its serene and solemn design, which reflects the spiritual significance of the site. The main chamber is surrounded by high vaulted corridors, adorned with four smaller domes placed on the roof.